Stereotactic Ablative Radiotherapy of Ventricular Tachycardia Using Tracking: Optimized Target Definition Workflow - Dvorak, Pavel; Knybel, Lukas; Dudas, Denis; Benyskova, Pavla; Cvek, Jakub (Frontiers in Cardiovascular Medicine, 2022)
Background and purpose Stereotactic Arrhythmia Radioablation (STAR) has been suggested as a promising therapeutic alternative in cases of failed catheter ablation for recurrent ventricular tachycardias in patients with structural heart disease. Cyberknife® robotic radiosurgery system utilizing target tracking technology is one of available STAR treatment platforms. Tracking using Implantable Cardioverter-Defibrilator lead tip as target surrogate marker is affected by the deformation of marker-target geometry. A simple method to account for the deformation in target definition process is proposed. Methods Radiotherapy planning CT series include scans at expiration and inspiration breath hold, and three free breathing scans. All secondary series are triple registered to the primary CT: 6D/spine + 3D translation/marker + 3D translation/target surrogate – a heterogeneous structure around the left main coronary artery. The 3D translation difference between the last two registrations reflects the deformation between the marker and the target (surrogate) for the respective respiratory phase. Maximum translation differences in each direction form an anisotropic Geometry Deformation Margin (GDM) to expand the initial single-phase clinical target volume (CTV) in order to create an internal target volume (ITV) in the dynamic coordinates of the marker. Alternative GDM based target volumes were created for seven recent STAR patients and compared to the original treated planning target volumes (PTV) as well as to analogical volumes created using deformable image registration (DIR) by MIM® and Velocity® software. Intra- and inter-observer variabilities of the triple registration process were tested as components of the final ITV to PTV margin. Results A margin of 2mm has been found to cover the image registration observer variability. GDM based target volumes are larger and shifted towards the inspiration phase relative to the original clinical volumes based on a 3 mm isotropic margin without deformation consideration. GDM based targets are similar (mean DICE similarity coefficient range 0.80-0.87) to their equivalents based on DIR of the primary target volume delineated by dedicated software. Conclusion The proposed GDM method is a simple way to account for marker-target deformation related uncertainty for tracking with Cyberknife® and better control of risk of target underdose. The principle applies to general radiotherapy as well.